Answer:
D (4,10)
Step-by-step explanation:
the answer is d
Answer:
x>-6
Step-by-step explanation:
The expression you need to solve for this is: 2x+15>3
For now pretend that the > is a = and solve as you normally would for x.
Subtract 15 from both sides
2x=-12
Divide by 2
x=-6
Put the > back in
x>-6
Answer:
Step-by-step explanation:
If these 3 points are collinear, then we can find the slope of the linear function using any 2 of those points. Suppose we use (-4, 3) and (0, 1):
As we move from (-4, 3) to (0, 1), x increases by 4 and y decreases by 2. Hence, the slope of this lilne is m = rise/run = -2/4, or m = -1/2.
Using the slope-intercept formula y = mx + b and replacing y with 1, x with 0 and m with -1/2, we get:
1 = (-1/2)(0) + b, or b = 1. Then the desired equation is y = f(x) = (-1/2)x + 1
Answer:
Wonka bars=3 and Everlasting Gobstoppers=24
Step-by-step explanation:
let the wonka bars be X
and everlasting gobstoppers be Y
the objective is to
maximize 1.3x+3.2y=P
subject to constraints
natural sugar
4x+2y=60------1
sucrose
x+3y=75---------2
x>0, y>0
solving 1 and 2 simultaneously we have
4x+2y=60----1
x+3y=75------2
multiply equation 2 by 4 and equation 1 by 1 to eliminate x we have
4x+2y=60
4x+12y=300
-0-10y=-240
10y=240
y=240/10
y=24
put y=24 in equation 2 we have'
x+3y=75
x+3(24)=75
x+72=75
x=75-72
x=3
put x=3 and y=24 in the objective function we have
maximize 1.3x+3.2y=P
1.3(3)+3.2(24)=P
3.9+76.8=P
80.7=P
P=$80.9
hey there
the answer is
14x + 6 = 5x + -3
6 + 14x = 5x + -5
6 + 14x = -3 + 5x
6 + 14x + -5x = -3 + 5x + -5x
Combine like terms: 14x + -5x = 9x
6 + 9x = -3 + 5x + -5x
Combine like terms: 5x + -5x = 0
6 + 9x = -3 + 0
6 + 9x = -3
6 + -6 + 9x = -3 + -6
Combine like terms: 6 + -6 = 0
0 + 9x = -3 + -6
9x = -3 + -6
Combine like terms: -3 + -6 = -9
9x = -9
Divide each side by '9'.
x = -1
Simplifying
x = -1
thank you
OFFICIALLYSAVAGE2003